Pick your yoga practice : exploring and understanding different styles of yoga - McCrary, Meagan (Novato, California : New World Library, 2013)
"Millions practice yoga, but what kind? Hatha, Ashtanga, Bikram, Iyengar? Hot room, flowing, or held postures, with or without meditation and chanting? And everyone practices for different reasons - weight loss, strength training, injury healing, relaxation. Those new to yoga should know they have choices (so as not to be put off by one bad fit), and regular practitioners should know that there are dozens of ways to expand or reinvigorate their routine. This is the first yoga book to help everyone interested understand all their options. Eight of the most prominent yoga approaches, plus ten "best of the rest," are explained in terms of what a class is like, level of physical exertion, and philosophical and spiritual underpinnings. As in the fairy tale, some may find some yoga too hot or too cold, too hard or too soft - but virtually everyone can find a yoga that is just right"--
"Helps readers understand their options among different styles of yoga. Profiles seven prominent styles in depth and ten others briefly, including their history, philosophical and spiritual underpinnings, level of physical exertion, and what to expect in a typical class"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Hatha yoga; Yoga; Exercise